Herbal preparations of plant materials and their role in phytotherapeutic treatment of acne - Shulezhko, Anastasiia; Maga, Ivan (Problems of Environmental Biotechnology, 2024)
The role of herbal preparations of plant materials in the phytotherapeutic treatment of acne is investigated